Criminological Review Of Commercial Sex Workers Regarding The Misuse Of Michat And Prevention Efforts In The City Of Gorontalo - Yayan Sahi; Sukarman Kamuli; Lucyane Djaafar (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract This research aims to examine the criminological aspects of commercial sex workers regarding the misuse of MiChat and prevention efforts in Gorontalo City. The research method used is qualitative with a case study approach. The research was conducted in hotels and lodging areas in Gorontalo City. The study involved 4 Commercial Sex Workers, 1 community leader, 1 representative from the PPA unit of Gorontalo City Police, and 1 representative from the Head of the Integrated Service Unit for Women and Children Empowerment of Gorontalo City as informants. The results of the study show that: (1) Women's motives for becoming commercial sex workers in Gorontalo City are driven by economic reasons, friends, boyfriends, and husbands; (2) Commercial sex workers use the MiChat application due to the availability of a wide range of customers using their services; (3) Public reaction to the presence of commercial sex workers in Gorontalo City causes anxiety among the local community; (4) Prevention efforts by the police and the Integrated Service Unit for Women and Children Empowerment of Gorontalo City in dealing with online prostitution cases still face various obstacles and have not been implemented to their fullest potential. The conclusion of this research is that in the context of criminology, the behavior of commercial sex workers who misuse the MiChat application is driven by economic and social motives. Keywords: Criminology, Commercial Sex Workers in Gorontalo City, MiChat Application.